Julio Mario Santodomingo Library’s Public Space - Wiesner, Diana (project baikal, 2013)
Public Libraries located in Bogotá the capital of the Republic of at 2650 m above sea level made a good contribution to public space in the northen districts with limited public and green spaces. More than a library public space offers possibilities to young people to have a nice green and permeable space full of native nature. The ultimate aim of the design is to contribute as a proposal in introducing biodiversity giving value to the spontaneous and wild forgotten species as well as recicled materials.
Keywords: public equipment; public space; green infrastructure; landscape ecology; urban biodiversity; public library; landscape design; Bogota; Colombia